Productividad y desarrollo regional: el caso de la subregión Ciénega de Zacapu - Gutiérrez Reyes, Ignacio (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The present study has the objective to determine the variables that affect the productivity of the region Ciénega de Zacapu, a territory that generated high expectations of productive development due to the expansion of the agricultural frontier and its early industrialization. Nevertheless, this increase in productivity has not been sustainable over time and it has been observed that since the year two thousand, other municipalities in the state of Michoacán with similar population growth rates and have had the highest results in terms of productivity. Based on a review of the literature on productivity a regional development, indicators that affect regional productivity were selected, which were grouped into six independent variables that serve as the basis for developing a regional productivity index. A total of 329 companies in the studied subregion of the three productive sectors were surveyed and the regional productivity index was calculated, which indicates that the Ciénega de Zacapu subregión has a level between low and regular. With this information, statistical analyzes were carried out such as frequencies, measures of central tendency a dispersion. The Pearson correlation coefficient was calculated, with which it was found that each of the proposed explanatory variables correlates positively at a level between media and considerable with the variable regional productivity.

La presente investigación tiene como objetivo determinar las variables que inciden en la productividad de la subregión Ciénega de Zacapu, un territorio que generó altas expectativas de desarrollo productivo debido a la expansión de la frontera agrícola y a su temprana industrialización. Sin embargo, este incremento de su productividad no ha sido sostenible en el tiempo y se observa que desde el año dos mil, otros municipios del estado de Michoacán de similar tamaño de población han tenido mejores resultados en cuanto a indicadores de productividad. Con base en una revisión de la literatura sobre productividad y desarrollo regional se seleccionaron indicadores que inciden en la productividad regional los cuales se agruparon en seis variables independientes que sirven de base para elaborar un índice de productividad regional. En la investigación se encuestó a un total de 329 empresas de la subregión estudiada de los tres sectores productivos y se calculó el índice de productividad regional que indica que la subregión Ciénega de Zacapu tiene un nivel entre bajo y regular. Con esta información se realizaron análisis estadísticos de frecuencias, medidas de tendencia central y de dispersión, asimismo se calculó el coeficiente de correlación de Pearson con lo que se encontró que cada una de las variables explicativas propuestas se correlacionan de manera positiva en un nivel entre medio y considerable con la variable productividad regional.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias del Desarrollo Regional
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2022-0603; Productividad Regional; Desarrollo Regional; Ciénega de Zacapu; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6773